Nutritional strategy for postpartum weight loss (Research, Society and Development, 2022)
Introduction: The postpartum period, is known as puerperium, in the postpartum in turn, causes the body to return to normal conditions, and is usually variable because of breastfeeding, this period blocks ovulation. It is believed that in the postpartum period, all organs, except the breasts, are already in a predicted condition, which are independent of breastfeeding. Objective: to present nutritional strategies for postpartum weight loss. Methodology: this is a literature review with descriptive approach, with articles published on digital platforms in the years 2011 to 2022, with the descriptors Obesity, postpartum, obesity in the postpartum period, nutritional strategies. Results and Discussion: Obesity is a body inflammation, termed as a chronic disease, acquired through inadequate eating habits, pregnant women tend to gain weight due to various factors of pregnancy, and to lose them after pregnancy costs about 4 to 6 weeks, and it is necessary to eat proteins of high biological value, and foods with low glycemic index. Conclusion: It is necessary that in the puerperium period the woman lives the guard, because during this period the organs return to their normal size. On food, it is necessary to balance in quantities and quality, for the energy balance to be positive.